2015
DOI: 10.1038/nature15382
|View full text |Cite
|
Sign up to set email alerts
|

Yap-dependent reprogramming of Lgr5+ stem cells drives intestinal regeneration and cancer

Abstract: The gut epithelium has remarkable self-renewal capacity that under homeostatic conditions is driven by Wnt signalling in Lgr5(+) intestinal stem cells (ISCs). However, the mechanisms underlying ISC regeneration after injury remain poorly understood. The Hippo signalling pathway mediates tissue growth and is important for regeneration. Here we demonstrate in mice that Yap, a downstream transcriptional effector of Hippo, is critical for recovery of intestinal epithelium after exposure to ionizing radiation. Yap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
599
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(655 citation statements)
references
References 34 publications
54
599
2
Order By: Relevance
“…The Hippo pathway may thus be implicated in the regenerative response of the pituitary stem cells, in agreement with its involvement in (stem cell-driven) repair in other tissues like the intestine (Gregorieff et al 2015) and heart (Heallen et al 2013, Xin et al 2013.…”
Section: Hippo Pathway: a New Player In Pituitary Stem Cell Regulation?mentioning
confidence: 60%
See 2 more Smart Citations
“…The Hippo pathway may thus be implicated in the regenerative response of the pituitary stem cells, in agreement with its involvement in (stem cell-driven) repair in other tissues like the intestine (Gregorieff et al 2015) and heart (Heallen et al 2013, Xin et al 2013.…”
Section: Hippo Pathway: a New Player In Pituitary Stem Cell Regulation?mentioning
confidence: 60%
“…repressing YAP/TAZ) may thus exert tumor-suppressive activity. The Hippo system may also interact with WNT signaling since Yap1 deletion blocked the development of adenomas in WNT-activated Apc −/− intestinal crypts (Gregorieff et al 2015). Implication of Hippo in pituitary tumorigenesis is still uncharted although enrichment of various Hippo pathway components (e.g.…”
Section: Dysregulation Of Hippo In Pituitary Tumorigenesis?mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that SFKs negatively regulate Wnt-␤-catenin signaling. Given that YAP is thought to inhibit the Wnt-␤-catenin signaling pathway (48)(49)(50), SFKs likely target this pathway through upregulation of YAP activity in crypt IECs. We also found that IEC-specific ablation of Csk increased the number of goblet cells in the ileum as well as in intestinal organoids and that expression of the Notch target genes Olfm4 and Hes1 (9, 51) was downregulated in crypts of Csk CKO mice ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that RSPOs cooperate with Wnts during development, particularly by promoting the transcriptional activity of β-catenin, which is an important mechanism of the Wnt signaling pathway (5,16). It has been revealed that canonical Wnt/β-catenin signaling serves an important role in numerous cancer types, including lung, breast, brain, colorectal and liver tumors (21)(22)(23). Interaction between RSPOs and LGR4, as well as the intracellular signaling proteins, promotes phosphorylation of LRP5/6, stabilizes β-catenin expression and promotes its transcriptional activity (18).…”
Section: Introductionmentioning
confidence: 99%